Preliminary Studi of Dye-Sensitized Solar Cell Photoelectrochemical for CO2 Conversion to Methanol Using CuO-modified Dark TiO2 Nanotubes Array as Cathode - Arda, Hany Dwi; Syauqi, Muhammad Iqbal; Gunlazuardi, Jarnuzi (Molekul, 2024)
The increased atmospheric carbon dioxide (CO2) levels can lead to climate change and adversely affect human health. Therefore, it is necessary to develop a method to capture CO2 and convert it into a more valuable substance, such as methanol. In this study, we established a tandem system involving dye-sensitized solar cells and photoelectrochemical (DSSC-PEC), which included the PEC zone using CuO/dark TiO2 nanotube array (CuO/dTNA) as the dark cathode where CO2 reduction takes place, and Co-Pi/blue TiO2 nanotube array (Co-Pi/bTNA) as the counter photoanode. For the DSSC zone, N719/TNA was used as the photoanode, I-/I3- electrolyte, and Pt/FTO as the cathode. The tandem system was constructed by connecting the PEC cathode to the DSSC photoanode and the PEC photoanode to the DSSC cathode using silver wire. Under solely visible light induction and water containing sodium bicarbonate electrolyte saturated with CO2, the proposed devise produced methanol at 1.292 μmol/hour. Keyword: Carbon dioxide, copper oxide, dark TiO2 nanotube, DSSC-PEC